PWE-047 Evaluation of PEG-IFN in an ethnically diverse HBV-infected population: 50% of treated patients derive long-term benefit. (23rd September 2015) - Ghani, R; Javaid, A; Marley, R; Lindsay, J; Kennedy, P T; Foster, G R
Abstract : Introduction: Historically pegylated-interferon (PEG-IFN) was reserved for HBeAg+ disease, where seroconversion represented a well defined treatment outcome with reported rates of up to 32%. 1 It has recently been shown to benefit a small proportion of patients with HBeAg- disease although patient groups who will benefit remains unclear. The Royal London Hospital treats a large ethnically diverse HBV infected population, thus represents an ideal setting to evaluate the influence of ethnicity on response. Methods: Chronic HBV patients completing treatment with PEG-IFN between 2005 and 2008 were included. A total of 34 patients received PEG-IFN alfa-2a (180 μg once weekly) for 48 weeks. ALT, HBeAg, anti-HBe and viral load (VL) were recorded at 24 and 48 weeks on treatment, 6 and 24 months post treatment. Patients were divided according to e antigen status; HBeAg+ (Group 1, n=25) and HBeAg-(Group 2, n=9). Treatment success was defined by HBeAg seroconversion for Group 1, and a viral load <80 IU/ml and ALT normalisation (<40 IU/l) 6 months after treatment cessation was considered treatment success for HBeAg negative patients (Group 2). Results: For HBeAg+ve patients (Group 1, n=25, 6 East Asian, 4 Bangladeshi, 5 African 6 other): 4 patients (17%) seroconverted, one of whom became anti-HBs+ on treatment. 28% of patients suppressed viral load and normalised ALT while on treatment. 50% of patients progressed to oral antivirals, 25% of whom then seroconverted. Hence 50% of patients either seroconverted or moved to a disease state where therapy was not required. All ethnic groups had a similar response and no pre-treatment factors influenced outcome. For HBeAg-ve disease (Group 2, n=9, 3 Bangladeshi 2 Pakistani 4 other): 3 patients (33%) met the criteria for treatment success at 48 weeks which was upheld over follow-up, one of whom underwent HBsAg seroconversion. Two patients had a sustained reduction in viraemia and inflammation that led to a decision to withhold further therapy. Four patients (44%) required oral antiviral therapy. Hence 56% of patients were managed by interferon alone. Success was most marked in patients from Bangladesh; all three had a full response. Conclusion: This study highlights the benefit of PEG-IFN in HBeAg- disease and its potential advantage in certain ethnic groups. Nevertheless, we saw lower seroconversion rates in HBeAg+ patients than previously reported. Our data suggest that a high ALT is not a requisite for treatment success, while baseline VL, fibrosis stage and age were not determinants of treatment outcome. These data suggest that consideration should be given to PEG-IFN as a treatment option, as opposed to the early initiation of lifelong oral antivirals in treating chronic HBV.